The Influence of Mental Health and Non-Phsycal Work Environment on Work Effectiveness - Suci Azzahra Adela; Kokom Komariah; Resa Nurmala (Dinasti International Journal of Education Management And Social Science, 2025)
Researchers found several problems faced by Generation Z workers, especially in the Pasirhalalang village area, one of the main reasons why many employees choose to leave their jobs and move to other jobs is a toxic work environment which causes employee absenteeism rates to increase. Employee work effectiveness is greatly influenced by the work environment and mental health. The method used is quantitative with a causal descriptive approach. Mental health and the non-physical work environment have a significant positive effect on work effectiveness. The mental health and non-physical work environment of generation Z workers in Pasirhalang Village have a good impact on employees, because both can be felt by employees, increasing work effectiveness as shown by the company providing satisfaction with the work it does and its employees. Able to follow workplace rules. . And through a non-physical work environment, Generation Z workers in Pasirhalang Village have high values which can be seen through good communication and always working together in teams, making employees develop creativity and innovation to help the company achieve its goals.